Anatomy of the economic value generated by a cultural event - Aguado, Luis F.; Heredia-Carroza, Jesús; Espinosa-Espinosa, Aaron; Garizado-Román, Paola A.; Duque-Sandoval, Henry (Journal of Business Economics and Management, 2024)
The article measures the economic effects of decisions made by two agents in the cultural and creative sector. Managers of a cultural event decide to produce it: it mobilizes a flow of artists and creatives who materialize their creations. Individuals decide to visit it: it mobilizes a flow of individuals who produce experiences by attending the event. The result is revealed by the economic dimension of the value generated by a cultural event: new income and jobs for the host territory of the event and unique and authentic cultural experiences for those attending the event. The empirical literature has drawn attention to the need for more precise measures of economic value, in particular that do not overestimate. A combination of instruments is used: interviews (n = 6) with event managers/organizers; a face-to-face survey (n = 173) with representatives of commercial stalls; a face-to-face survey of attendees (n = 1,030); and, an input–output model is adapted to the area of impact. The article provides a methodologically useful framework for identifying and estimating more reliable measures of the material (economic) value created by a cultural event, which can be replicated in a variety of events around the world.